2018
DOI: 10.1002/bit.26575
|View full text |Cite
|
Sign up to set email alerts
|

Peptide ligand‐mediated endocytosis of nanoparticles to cancer cells: Cell receptor‐binding‐ versus cell membrane‐penetrating peptides

Abstract: The endocytosis-mediating performances of two types of peptide ligands, cell receptor binding peptide (CRBP) and cell membrane penetrating peptide (CMPP), were analyzed and compared using a common carrier of peptide ligands-human ferritin heavy chain (hFTH) nanoparticle. Twenty-four copies of a CMPP(human immunodeficiency virus-derived TAT peptide) and/or a CRBP (peptide ligand with strong and specific affinity for either human integrin(α β ) or epidermal growth factor receptor I (EGFR) that is overexpressed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Particles with less negative surface charge interact more with cells compared to those with more negative charge, owing to the negative charge of the cell membrane. Therefore, the chance of NPs binding to and penetrating cells is increased [43]. Also, research has shown that larger particles are more easily endocytosed than small particles, resulting in higher cellular cytotoxicity [44].…”
Section: Resultsmentioning
confidence: 99%
“…Particles with less negative surface charge interact more with cells compared to those with more negative charge, owing to the negative charge of the cell membrane. Therefore, the chance of NPs binding to and penetrating cells is increased [43]. Also, research has shown that larger particles are more easily endocytosed than small particles, resulting in higher cellular cytotoxicity [44].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the efficiency in drug delivery of nanoparticles can be associated to the uptake by the targeted cells, with transport through the plasmatic membrane. Thus, membrane-penetrating nanoparticles may provide advantageous application properties for improved targeted drug delivery [10][11][12][13][14]. In the gastrointestinal tract, endocytose has been described as the major mechanism of absorption of nanoparticles by translocating the intestinal lymph node (Peyer's patches) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the efficiency in drug delivery of nanoparticles can be associated with the uptake by the targeted cells, with transport through the plasmatic membrane. Thus, membrane-penetrating nanoparticles may provide advantageous application properties for improved targeted drug delivery. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the efficiency in drug delivery of nanoparticles can be associated to the uptake by the targeted cells, with transport through the plasmatic membrane. Thus, membrane-penetrating nanoparticles may provide advantageous application properties for improved targeted drug delivery [10][11][12][13][14]. In the gastrointestinal tract, endocytose has been described as the major mechanism of absorption of nanoparticles by translocating the intestinal lymph node (Peyer's patches) [15,16].…”
Section: Introductionmentioning
confidence: 99%